Pair-work dynamics: Stronger learners' languaging engagement and learning outcomes for the Japanese polysemous particles ni/de. (30th April 2018) - Masuda, Kyoko; Iwasaki, Noriko
Abstract : Adopting microgenetic analysis of languaging (Swain, 2006) in pair-work, this study aims to advance our understanding of learners' developmental processes for the complex concepts of Japanese particles ni/de. Two pairs whose learning outcomes differed were chosen, and their languaging was examined, focusing on 'stronger' learners, the peers who showed more target-like knowledge of particles on fill-in-theblank pre-test than their partners. Both interaction patterns and quality of engagement appeared to have facilitated their conceptual internalization for the Japanese particles ni/de. A stronger learner in one of the pairs demonstrated reciprocal elaborate engagement in a collaborative pattern, and greatly improved his understanding and retained it longer-term. In contrast, a stronger learner in the other pair, who demonstrated non-reciprocal limited engagement in dominant-passive interaction, showed no development over time. Follow-up interviews revealed these peers' differing attitudes toward pair-work, which were likely conducive to their engagement in pair-work and L2 learning outcome.